IAENG transactions on engineering sciences special Issue for the International Association of Engineers Conferences - Ao, Sio-Iong; Chan, Alan Hoi-Shou; Katagiri, Hideki; Xu, Li (World Scientific, 2015)
Two large international conferences on Advances in Engineering Sciences were held in Hong Kong, March 12 14, 2014, under the International MultiConference of Engineers and Computer Scientists (IMECS 2014), and in London, UK, 2 4 July, 2014, under the World Congress on Engineering 2014 (WCE 2014) respectively. This volume contains 37 revised and extended research articles written by prominent researchers participating in the conferences. Topics covered include engineering mathematics, computer science, electrical engineering, manufacturing engineering, industrial engineering, and industrial applications. The book offers tremendous state-of-the-art advances in engineering sciences and also serves as an excellent reference work for researchers and graduate students working with/on engineering sciences